The impact of processing on soy allergenicity: A comprehensive bibliometric analysis - Triandita Nanda; Prangdimurti Endang; Yuliana Nancy Dewi; Wijaya Hendra; Palupi Nurheni Sri (BIO Web of Conferences)
The objective of this study is to conduct a bibliometric analysis of the impact of various processing techniques to decrease soy allergenicity. Data were collected from the Scopus database, encompassing the years 2000 to 2023, utilizing the keywords “processing” and “soy allergen.” A total of 111 articles were analyzed using Biblioshiny and VOSviewer, with a focus on how processing methods affect soybean allergens. The analysis revealed that China is the leading contributor in terms of publications and international collaborations, particularly with institutions such as Henan University of Technology and China Agricultural University. The findings indicate that processing methods, including heating, fermentation, and enzymatic hydrolysis, can reduce the allergenic potential of soy. This study provides valuable insights for the development of safer soy-based products for individuals with allergies and underscores the necessity for further research into the mechanisms underlying changes in allergenicity due to processing. These findings are expected to inspire innovations in soy-based food products and contribute to food safety policies.